Effect of climate therapy and rehabilitation in Mátra Medical Institute - Müller, Anetta; Kerényi, Erika; Könyves, Erika (Applied Studies in Agribusiness and Commerce, 2011)
Our research we organised at the Mátra Medical Institute in Mátraháza and Kékestetô among sick of asthma, COPD and hayfever. Our aim was to prove the effect of climate therapy in the Mátra Medical Institute. The subalpine climate to plays a very important role in the cure of the Respiratory diseases, because to improve the life quality of the sick and reduce the medicine uses afther the therapy. Our researche took part more than 100 respiratory diseased. We analyse the data with SPSS.version16. We measure average, standard deviation, Chi²probe, t-probe.You can see our results in the article.